HYPOTHESIS ABOUT THE CUT SURFACE - MACUROVÁ, Anna; VASILKO, Karol (Trends in education, 2008)
In the paper is presented the hypothesis with testing experimental process.
Keywords: Hypothesis; surface; testing of the hypothesis.